Призначення та проведення експертиз: проблеми законодавства і практики - Наумова, А. О.; Naymova, A. O.; ORCID: http://orcid.org/0000-0002-4273-8068; Куча, М. С.; Kucha, M. S.; ORCID: http://orcid.org/0000-0002-9308-9301 (Вісник Харківського національного університету внутрішніх справ. – 2019. – № 3 (86). – С. 80-88, 2019)
Розглянуто проблемні питання призначення та проведення експертизи, обґрунтовано необхідність унормування процесуальної процедури призначення повторної та додаткової експертиз. Проаналізовано практику призначення та проведення вибухотехнічних експертиз, надано рекомендації щодо підготовки експертних об’єктів.

It has been noted that the problems of procedural guaranteeing of the rights of victims, suspects (accused) in terms of reforming the criminal procedural legislation are relevant during the appointment and holding of the examination and require further research. The aim of this study is to analyze the current criminal procedural legislation on the appointment and conduction of examination and to develop propositions for its improvement. The authors of the article have analyzed the existing procedural legislation on the appointment and conduction of examination; have defined the problematic issues of procedural guaranteeing of the rights of victims, suspects (accused) in the appointment and conduction of examination; and have offered the ways to solve them; have substantiated the need for legislative regulation of additional and re-examination of explosive and technical examination and have provided forensic recommendations to eliminate these problems. Based on the conducted research, the authors have provided the following suggestions and recommendations: 1) to enshrine the right of the prosecution and defense parties in the Art. 243 of the Criminal Procedural Code of Ukraine (CPC) to independently appoint an examination; 2) to declare it appropriate to supplement Section 3 of the CPC with the Art. 56-1 “Rights of the victim in the appointment and conduction of examination”, which should enshrine the relevant rights; 3) to declare it expedient to supplement Section 20 of the CPC of Ukraine with the Art. 242-1, which should determine the rights of the suspect (accused) in the appointment and conduction of examination; 4) to standardize the procedure for the appointment of additional expertise in paragraph 11 of the Art. 101 of the CPC; 5) to standardize the procedure for the appointment of re-examination in paragraph 12 of the Art. 101 of the CPC; 6) to recommend investigators and judges to determine the expert’s questions depending on the objects of expert examination; 7) to improve the stage of experimental testing of objects in carrying out explosive examination.

Рассмотрены проблемные вопросы назначения и проведения экспертизы, обоснована необходимость нормирования процессуальной процедуры назначения повторной и дополнительной экспертиз. Проанализирована практика назначения и проведения взрывотехнической экспертизы, даны рекомендации по подготовке экспертных объектов.
Appointment and Conduction of Examinations: Legislative and Practical Problems
Наумова, А. О. Призначення та проведення експертиз: проблеми законодавства і практики / Анна Олександрівна Наумова, Максим Сергійович Куча // Вісник Харківського національного університету внутрішніх справ. – 2019. – № 3 (86). – С. 80-88. - DOI: https://doi.org/10.32631/v.2019.3.08.
Наумова, А. О. і Куча, М. С. (2019) «Призначення та проведення експертиз: проблеми законодавства і практики», Вісник Харківського національного університету внутрішніх справ, 86(3), с. 80-88. doi: 10.32631/v.2019.3.08.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; експертизи; потерпілий; підозрюваний; додаткова експертиза; повторна експертиза; вибухотехнічна експертиза; призначення експертизи; экспертиза; потерпевший; подозреваемый; дополнительная экспертиза; повторная экспертиза; взрывотехническая экспертиза; examination; victim; suspect; additional examination; re-examination; explosive examination